A Fast HPLC/UV Method for Determination of Ketoprofen in Cellular Media - Vozniuk, Oleksandra; Kejík, Zdeněk; Veselá, Kateřina; Skaličková, Markéta; Novotný, Petr; Hromádka, Róbert; Hajduch, Jan; Martásek, Pavel; Jakubek, Milan (ChemistryOpen, 2024)
A simple, sensitive and quick HPLC method was developed for the determination of ketoprofen in cell culture media (EMEM, DMEM, RPMI). Separation was performed using a gradient on the C18 column with a mobile phase of acetonitrile and miliQ water acidified by 0.1 % (v/v) formic acid. The method was validated for parameters including linearity, accuracy, precision, limit of quantitation and limit of detection, as well as robustness. The response was found linear over the range of 3-100 μg/mL as demonstrated by the acquired value of correlation coefficient R2=0.9997. The described method is applicable for determination of various pharmacokinetic aspects of ketoprofen in vitro.
Keywords: indikátory a reagencie; vysokoúčinná kapalinová chromatografie; Ketoprofen; Chromatography, High Pressure Liquid; HPLC/UV; ketoprofen; cellular medium; Indicators and Reagents